Dispersion evaluation of hydrogen sulfide inclusion in a cryogenic distillation pilot plant - Mohd Shukor, Mohd Syazwan; Omar, Rozita; Abdul Hamid, Mohamad Rezi; Harun, Mohd Razif; Md Said, Mohamad Syazarudin (John Wiley and Sons Inc, 2024)
A risk analysis simulation was completed for a cryogenic distillation (Cryo-D) pilot operation processing a natural gas feed stream containing H2S. This study placed significant H2S concentration inside the Cryo-D and evaluated its dispersion after a simulated leak within the pilot plant. Sensitivity analysis using an in-house process simulation identified the operating conditions that caused the highest surroundings H2S concentration. A computational fluid dynamic (CFD) dispersion simulation assessed H2S leakage at the bottom column section and its effects on operators. A case with 60 bar column pressure, −30°C inlet temperature and 10% H2S input gas had the highest mass flow rate of 4.74 kg/h H2S through a leak. Leaked H2S covers 50% of the building within 60 s. Within 120 s, H2S accumulates toward the column bottom. At 120 s, most operators are exposed to above 1000 ppm H2S, which may cause fatalities instantly. Recommendations include enhancing the ventilation of the building by installing ventilation near the base of the cryogenic column in order to lessen the exposure concentration. In conclusion, H2S leakage from an indoor Cryo-D pilot plant can cause catastrophic consequences due to its rapid dispersion and accumulation throughout the building. © 2024 American Institute of Chemical Engineers.